Unlocking the potential of railways a railway strategy for CAREC, 2017 2030. (Metro Manila, Philippines Asian Development Bank, 2017)
This publication provides a blueprint for sound, long term development of CAREC railways into a quick, efficient, and accessible transport system. The 2017 2030 CAREC railway strategy intends to equip the region railways to better capture evolving trade flows and contribute to regional economic development by improving rail and multimodal infrastructure and commercializing and reforming railway activities.
Keywords: Industry and state; Social rights -- Asia; Electronic books